2013
DOI: 10.1038/cmi.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Selective expansion of human natural killer cells leads to enhanced alloreactivity

Abstract: In allogeneic stem cell transplantation (SCT), natural killer (NK) cells lacking their cognate inhibitory ligand can induce graft-versus-leukemia responses, without the induction of severe graft-versus-host disease (GVHD). This feature can be exploited for cellular immunotherapy. In this study, we examined selective expansion of NK cell subsets expressing distinct killer immunoglobulin-like receptors (KIRs) within the whole human peripheral blood NK cell population, in the presence of HLA-Cw3 (C1) or Cw4 (C2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…We did not find any associations between the infused dose of various immune cell subsets and the clinical outcome of the recipients, and results from previous studies of associations between cell subset dose and outcome are also conflicting ( 29 , 30 , 33 , 48 50 ). Our present results support previous studies suggesting that the balance between different immunocompetent cell subsets is important ( 31 , 32 , 37 , 51 ) and in addition our results suggest that the broader immunocompetent cell subset profile as well as the dose-independent responsiveness to G-CSF (i.e., the increase in the concentrations of various subsets, Figure 4 ) are more important than differences in single cell subset levels.…”
Section: Discussioncontrasting
confidence: 84%
“…We did not find any associations between the infused dose of various immune cell subsets and the clinical outcome of the recipients, and results from previous studies of associations between cell subset dose and outcome are also conflicting ( 29 , 30 , 33 , 48 50 ). Our present results support previous studies suggesting that the balance between different immunocompetent cell subsets is important ( 31 , 32 , 37 , 51 ) and in addition our results suggest that the broader immunocompetent cell subset profile as well as the dose-independent responsiveness to G-CSF (i.e., the increase in the concentrations of various subsets, Figure 4 ) are more important than differences in single cell subset levels.…”
Section: Discussioncontrasting
confidence: 84%
“…-NK cells were found to have a negative prognostic implication when lower than 115 cells/mm 3 . This finding points to the protective effect that NK cells have in cGvHD pathophysiology; it was demonstrated (42) that NK cells mediate the reduction of GvHD by inhibiting activated, alloreactive T cells while retaining graft-versus-tumor effects through effector molecules such as FasL (43). Thus, similarly to T cells, NK cells display a potent anti-leukemia effector capacity, and yet, unlike them, do not mediate cGvHD (44).…”
Section: Discussionmentioning
confidence: 97%
“…Differences in the starting population and in culture methods used to expand cells likely account for why more phenotypically mature NK cells were expanded using our system. Several groups have investigated the functional properties of expanded UCB NK cell populations 41,42 . Prior studies have shown that UCB derived CD56 + cells have low cytotoxic activity compared to their peripheral blood counterparts 43 , however their function can be augmented by IL-2 or IL-15.…”
Section: Discussionmentioning
confidence: 99%